(untitled) (London Journal of Engineering Research, 2024)
This article summarizes, partly as a glossary and partly as a compilation, the main concepts involved in the theory of architectural structures. It contains a holistic arrangement of the theoretical foundations of the main components of materials mechanics and, above all, their interaction with architecture, in the exercise of the so-called structural calculation. In thematic literature, it is not easy to find all this information gathered in simple, plain language. Hence the importance of reviewing, in a relatively simple and quick reading, the principles that lead to the epistemology of structural theory.